IoT-Based Wheel Chair for Fall Detection and Health Monitoring - Dr. C. R. Rathish; Dr. Sivaramakrishnan S (Research Parks Publishers, 2022)
The IoT-based wheelchair fall detection and health care system is used to detect when a patient is fallen from the wheelchair. When a patient has fallen out of their wheelchair, the IoT-based wheelchair fall detection and health care system is utilized to determine when this has occurred. When there is a need for the patient, the accelerometer sensor is engaged by hand movement. The message is then communicated to the appropriate person via text or phone, and the need is satisfied. It is possible to automate the light and fan with your voice using voice recognition. This technology provides continuous monitoring of the patient's temperature and pulse.